2014
DOI: 10.7828/jmds.v3i1.623
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Preparedness for Natural Disasters in Ozamiz City, Philippines

Abstract: The Philippines is identified as a natural disaster hot-spot and is ranked third among the most disaster risk countries in the world. Typhoons and tropical storms, flood, and earthquakes continue to cause thousands of human deaths and injuries in the country despite efforts of various organizations to intensify strategies for disaster risk reduction. Next to impacts on people, destructions in the critical infrastructure are often the most-compelling concerns in the aftermath of a disaster. This paper looked in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In relation to this, Galindo et al (2012) also emphasized in their study that disaster preparedness results in a more effective response to disasters, better coordination during disasters, and a speedier recovery from a disaster. However, results showed that organizations are perceived to be less prepared to moderately prepared when it comes to natural disasters as reflected in the average weighted values.…”
Section: Disaster Preparedness In the Philippinesmentioning
confidence: 99%
“…In relation to this, Galindo et al (2012) also emphasized in their study that disaster preparedness results in a more effective response to disasters, better coordination during disasters, and a speedier recovery from a disaster. However, results showed that organizations are perceived to be less prepared to moderately prepared when it comes to natural disasters as reflected in the average weighted values.…”
Section: Disaster Preparedness In the Philippinesmentioning
confidence: 99%
“…Factors that the public considers in reacting to a disaster warning include the significance of and understanding of the threat, and confidence (or lack thereof) in authorities. Initially, people make the determination whether or not the threat is real, and they trust the source of information before taking action [18][19][20][21][22][23][24][25][26][27].…”
Section: Degree Of Preparedness According To Selected Variablesmentioning
confidence: 99%